2022
DOI: 10.3389/fsurg.2022.893429
|View full text |Cite
|
Sign up to set email alerts
|

Better Prognosis and Survival in Esophageal Cancer Survivors After Comorbid Second Primary Malignancies: A SEER Database-Based Study

Abstract: BackgroundWith the development of surgical techniques and advances in systemic treatments, the survival time of esophageal cancer survivors has increased; however, the chance of developing a second primary malignancy (SPM) has also increased. These patients’ prognosis and treatment plans remain inconclusive.ObjectivesWe aimed to evaluate and predict the survival of patients with esophageal cancer with second primary tumors, to provide insights and the latest data on whether to pursue more aggressive treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
5
1
Order By: Relevance
“…The incidence of second cancers in gastric cancer has been reported by the IARC definition as being 1.3% 31) , 8.1% 32) , 0.5% 33) , and 12.9% by the SEER definition 34) . Ye et al reported that patients with esophageal MPM (+) had a better prognosis than those with MPM (-) 35) , similar to our results. However, the authors did not explain the mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of second cancers in gastric cancer has been reported by the IARC definition as being 1.3% 31) , 8.1% 32) , 0.5% 33) , and 12.9% by the SEER definition 34) . Ye et al reported that patients with esophageal MPM (+) had a better prognosis than those with MPM (-) 35) , similar to our results. However, the authors did not explain the mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the overall 3‐year survival rate (2.4%) was lower in the Ethiopian study compared to our setting (56%) 35 . Despite this, the mean survival time was longer in western countries than the African esophageal cancer patients 36–39 . These disparities suggested that cancer care was not adequate in African countries.…”
Section: Discussioncontrasting
confidence: 64%
“…35 Despite this, the mean survival time was longer in western countries than the African esophageal cancer patients. [36][37][38][39] These disparities suggested that cancer care was not adequate in African countries. Therefore, for better outcomes in cancer care, an improvement in treatment and diagnostic facilities should be the utmost priority of the health care delivery system, especially in the sub-Saharan African setting.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is attributed to the high fatality rate if cancer relapses in cured patients . An enhanced prognosis can guarantee a better survival rate among esophageal cancer patients up to 74.67 months of median survival time . Furthermore, studies have shown that there is a long-term prognosis risk, with complete recovery in cancer patients ranging from 5 years and above .…”
Section: Introductionmentioning
confidence: 99%
“…1 An enhanced prognosis can guarantee a better survival rate among esophageal cancer patients up to 74.67 months of median survival time. 2 Furthermore, studies have shown that there is a long-term prognosis risk, with complete recovery in cancer patients ranging from 5 years and above. 3 Unfortunately, the current prognosis of cancer depends heavily on limited clinical resources, which could hamper prognosis efficiency.…”
Section: Introductionmentioning
confidence: 99%